2019
DOI: 10.3390/app9061060
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Techniques to Predict the Mechanical Properties of Polyamide 2200 (PA12) in Additive Manufacturing

Abstract: Additive manufacturing (AM) is an attractive technology for the manufacturing industry due to flexibility in its design and functionality, but inconsistency in quality is one of the major limitations preventing utilizing this technology for the production of end-use parts. The prediction of mechanical properties can be one of the possible ways to improve the repeatability of results. The part placement, part orientation, and STL model properties (number of mesh triangles, surface, and volume) are used to predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Polyamides are well-known polymers and are widely used in engineering applications. A polyamide used so far, mainly in selective laser sintering (SLS) and binder jet technologies of AM, is polyamide 12 (PA12) [ 29 , 43 ] PA12 is a material that can be employed in many implementations due to its thermomechanical properties. It is not widely used in MEX implementations yet, with its filament market share being significantly lower than other materials [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamides are well-known polymers and are widely used in engineering applications. A polyamide used so far, mainly in selective laser sintering (SLS) and binder jet technologies of AM, is polyamide 12 (PA12) [ 29 , 43 ] PA12 is a material that can be employed in many implementations due to its thermomechanical properties. It is not widely used in MEX implementations yet, with its filament market share being significantly lower than other materials [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baturynska et al. successfully predicted the tensile modules and nominal stress of polymer powder bed fusion through the Gradient boosting regressor, Decision tree regressor and AdaBoost regressor [13] . Meanwhile, Zhan and the co‐workers found that random forest (RF) exhibited the highest accuracy to predict the fatigue life of printed stainless steel 316L, compared to artificial neural network (ANN) and support vector machine (SVM) methods [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 12 (PA12) is a popular polyamide, due to its enhanced thermal and mechanical response [ 8 ]. This specific grade has been investigated and applied in different additive manufacturing (AM) processes, such as binder jetting [ 9 ], powder bed fusion [ 10 , 11 ], and material extrusion (MEX) as pure material, or as the matrix material in composites [ 5 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. PA12 is a material suitable for the 3D printing (3DP) process, due to its rheological characteristics [ 22 ], its toughness, and high strain values before its failure [ 10 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%